The effect of 12-week combined balance and plyometric training on dynamic balance and lower extremity injury risk in college dancers - Yuqi Yan; Park Seoyoung; Heo Seomyeong; Yi Zhao (Frontiers in Physiology)
BackgroundDancers face significant physical demands and are at high risk for lower extremity injuries due to the complexity and intensity of their movements, which require strong dynamic balance. Improving dynamic balance through training can potentially enhance performance and reduce injury risk.ObjectiveThis study aimed to investigate the effects of a 12-week combined balance and plyometric training program (BP) compared to plyometric training alone (PL) on dynamic balance and lower extremity injury risk among college dancers.MethodsA total of 30 female college dancers were randomly assigned to either the BP group (n = 15) or the PL group (n = 15). Both groups participated in a 12-week training program, with the BP group engaging in both balance and plyometric exercises, and the PL group performing only plyometric exercises. Dynamic balance was assessed using the Dynamic Posture Stability Index (DPSI). Lower extremity injury risk was evaluated using the Limb Symmetry Index (LSI) and Center of Pressure (COP) measurements, pre- and post-intervention.ResultsThe BP group showed significant improvements in dynamic balance compared to the PL group, with a reduction in DPSI values (DF-DPSI: p < 0.001, partial η2 = 0.625; DL-DPSI: p < 0.001, partial η2 = 0.559). Additionally, the BP group showed significant reductions in COP displacements, particularly in the anterior-posterior direction (DF-COPAP: p < 0.015, partial η2 = 0.101; DL-COPAP: p = 0.019, partial η2 = 0.094). The BP group also demonstrated greater improvements in LSI-3C and LSI-6, which reflect dynamic stability (LSI-3C: p < 0.001, partial η2 = 0.229; LSI-6: p = 0.006, partial η2 = 0.128).ConclusionThe 12-week combined balance and plyometric training program was more effective than plyometric training alone in improving dynamic balance and reducing lower extremity injury risk in college dancers. This combined training approach is recommended for improving performance and preventing injuries in dancers.